Mitigating the effect of drought stress on yield in wheat (Triticum aestivum) using arbuscular mycorrhiza fungi (Glomus mosseae) - RANI, BABITA; MADAN, SHASHI; POOJA, POOJA; SHARMA, K D; KUMARI, NISHA; KUMAR, ASHWANI (The Indian Journal of Agricultural Sciences, 2018)
The arbuscular mycorrhiza fungus (AMF) (Glomus mosseae) is a beneficial microorganism used in agriculture as an efficient tool to improve plant growth and nutrition by inducing symbiotic association with crops. The present investigation was conducted to study the contribution of arbuscular mycorrhizal fungus to drought tolerance in wheat (Triticum aestivum L.) grown under normal irrigated conditions and in water stress created by withholding irrigation at jointing and heading stage under net house environment. Wheat seeds of two wheat varieties WH 1025 and WH 1105 were grown in pots after treatment with or without the AMF. Under water stress conditions, the wheat variety WH 1025 performed better in terms of growth and yield attributes as compared to WH 1105. The results obtained showed a significant improvement by AMF on plant height, number of productive tillers, spike length, number of spikelet, grain/spike, grain weight/spike and test weight under both irrigated and drought stress condition. Biomass and grain yields were higher in plants treated with mycorrhiza than non-mycorrhizal plants of both the varieties irrespective of soil moisture. Therefore, the results suggest that mycorrhizal inoculation play a vital role in improving growth and yield in wheat by reducing the effects of drought stress and sustain the wheat crop under the semi-arid environments.